Uji Model Fisik Kapasitas Aliran Pada Lubang Pengisian Tampungan Di Bawah Saluran Drainasi (Underdrain Box Storage) - Kuncoro, Yudo Tri; Sisinggih, Dian; Priyantoro, Dwi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
This paper discusses the results of a physical modelling of drainage channel where the holes at the bottom were arranged along the channel to fill the storage underneath. This research could be the initial step to get a formulation of flow capacity through drainage channel’s orifice, and expected to push further research. The results show that it is necessary take corrections to the formulation of flow through an orifice of tank in order to estimate flow through an orifice with horizontal flow. Formulation of flow capacity through orifice with horizontal flow above can be approximated by the relationship curves between Fr (Froude) and Q 2 / (h 1 5 .g) 1/2 as well as between Fr and a/h1 2Keywords: physical modelling, flow capacity, underdrain box storage